산업단지 인근 안산 도심지의 VOCs 분포 특성 - 신수현; 박종성; 김종범; 김필호; 김창혁; 황규철; 박승명; 이재영; 박정민; 김정호 (환경분석과 독성보건, 2024)
There are four industrial complexes located around Ansan City, which is one of the areas with the highest VOCs emissions in Gyeonggi region based on the emissions provided by the clean policy support system (CAPSS), Korea. In this study, proton transfer reaction time-of-flight mass spectrometer (PTR-TOF-MS) was used to determine the distribution of volatile organic compounds (VOCs) in urban areas near industrial complexes in Ansan City in 2023 (May to June). The PTR-TOF-MS was operated over the mass range of 10-400amu at a drift tube pressure of 2.3mbar and temperature 80o C (E/N ~ 130Td) that enabled the collection of VOC data at 0.1Hz resolution. The mixing ratio calculations for methanol, acetaldehyde, acetonitrile, acetone, acetic acid, dimethyl sulfide, isoprene, methyl vinyl ketone (MVK), methyl ethyl ketone (MEK), benzene, toluene, styrene, xylene, trimethylbenzene and pinene reported in this study were done using the sensitivity factors obtained from the PTR-TOF-MS calibrations. As a result of the intensive measurement in springtime, among the substances constituting VOCs, methanol was the most abundant with 16.27±7.13 ppb, followed by acetone, acetaldehyde, acetic acid, methyl ethyl ketone (MEK), toluene, and xylene. VOCs compositions were dominated by oxidized VOCs, with CxHyO1 at 74%, CxHyO2 at 11%, aromatic CxHy at 10.5%, and CxHyN at 3.1%, respectively. As a result of the diurnal variations and conditional probability function (CPF) analysis, it was found that toluene and MEK were locally greatly influenced by industrial complexes distributed around Ansan City. Related with the ozone creating contribution, the ratio of VOCs to nitrogen oxide (NOx) was 6.5 (1.4 to 18.2), which appeared in the NOx-limited (4:1) and the VOCs-limited (15:1). Therefore it is suggested that the management of emission source NOx and VOCs are very important for the reduction of ozone in Ansan.
Keywords: VOCs; PTR-ToF-MS; VOCs/NOx; Ansan